Pengaruh Financial Socialization dan Financial Attitude Terhadap Financial Satisfaction Melalui Financial Behavior Mahasiswa Rantau di Pulau Jawa - Nabila Resia Isnaini; Umi Widyastuti; M. Edo Suryawan Siregar (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to analyze the influence of financial socialization and financial attitude on financial satisfaction through financial behavior among non-local students in Jawa Island. The research involved a sample of 230 active students aged 18–25 years had migrated to Java Island for their studies. The sampling technique used was purposive sampling and the data were processed using the Covariance-Based Structural Equation Modeling (CB-SEM) method. The results show that financial socialization has a positive and significant effect on financial satisfaction, while financial attitude has no effect on financial satisfaction. Both financial socialization and financial attitude have a positive and significant effect on financial behavior. Furthermore, financial behavior positively and significantly influences financial satisfaction and mediates the relationship between financial socialization and financial satisfaction, as well as between financial attitude and financial satisfaction.